Antimicrobial activity of aqueous extract of Terminalia chebula Retz. - Jinukuti, Mary Grace; Giri, Archana (Recent Research in Science and Technology, 2014)
Terminalia chebula belonging to the family Combretaceae is called the "king of medicines" in Tibet and used in the treatment of various diseases such as diabetes, depression, memory loss, cardiovascular diseases, leprosy etc and also inhibits the growth of malignant tumors. T.chebula fruit is rich in phytochemical constituents such as tannins, flavonoids and essential oils. In the present study antimicrobial activity of aqueous fruit extract of T.chebula was evaluated by Agar well diffusion method against gram +ve (Bacillus sphaericus, Staphylococcus aureus), gram -ve (Pseudomonas aeruginosa, Proteus mirabilis, Salmonella typhimurium, Klebsiella pneumoniae, Proteus vulgaris, Escherichia coli) and fungal (Candida albicans) strains at different concentrations. Among the microbial strains evaluated P.mirabilis and K.pneumoniae were found to be the most sensitive, based on the results demonstrated from the inhibition zones. Thus, T.chebula fruit can be considered as a potential candidate for new antimicrobial drugs owing to its broad spectrum activity.